2008
DOI: 10.2147/ndt.s2330
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI evidence for language plasticity in adult epileptic patients: Preliminary results

Abstract: The present fMRI study explores the cerebral reorganisation of language in patients with temporal lobe epilepsy, according to the age of seizures onset (early or late) and the hippocampal sclerosis (associated or not). Seven right-handed control volunteers and seven preoperative adult epileptic patients performed a rhyme decision (language condition) and a visual detection (control condition) tasks in visually presented words and unreadable characters, respectively. All patients were left hemisphere dominant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
8
1
Order By: Relevance
“…In addition to alterations in hemispheric dominance in patients with TLE, there is evidence of intrahemispheric reorganization of language. Several studies have reported increased prefrontal activation, which may reflect compensatory processes given that it is seen when performance is unimpaired [ 82 , 83 ]. Such findings suggest alterations in the components and operation of language networks in TLE, and recent studies have examined directly the connectivity of nodes within these networks.…”
Section: Fmri For Languagementioning
confidence: 99%
“…In addition to alterations in hemispheric dominance in patients with TLE, there is evidence of intrahemispheric reorganization of language. Several studies have reported increased prefrontal activation, which may reflect compensatory processes given that it is seen when performance is unimpaired [ 82 , 83 ]. Such findings suggest alterations in the components and operation of language networks in TLE, and recent studies have examined directly the connectivity of nodes within these networks.…”
Section: Fmri For Languagementioning
confidence: 99%
“…In addition to more thorough surgical mapping, the benefit of this interactive assessment would be to better understand and predict brain plasticity. Namely, inter and intra-hemispheric cerebral reorganization (Baciu and Perrone-Bertolotti 2015;Berl et al 2014;Cousin et al 2008;Dupont 2000;Powell et al 2007;Rosenberger et al 2009;Sidhu et al 2013) in TLE patients can arise due to chronic epilepsy and surgery. The important point is that the reorganization of language can depend on regions that have not classically been considered a part of that network (Tracy and Boswell 2008) such as the hippocampus (Baciu and Perrone-Bertolotti 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous fMRI studies investigating the functional networks of working memory illustrated that amelioration of activation of mesiotemporal lobes contributed to effective task performance (56, 57). This may occur as part of a brain activity resource redistribution from task-irrelevant to task-relevant cortices in order to reduce interference (58).…”
Section: Role Of Pharmao-fmri Studies In Epilepsymentioning
confidence: 99%